Betaine Supplementation: A Critical Review of Its Efficacy for Improving Muscle Strength, Power, and Body Composition. Issue 4 (August 2021) - Van Every, Derrick W.; Plotkin, Daniel L.; Delcastillo, Kenneth; Cholewa, Jason; Schoenfeld, Brad J.
Abstract : ABSTRACT: Dietary supplements are commonly used by athletes to optimize body composition and/or performance in sport. Trimethylglycine, better known as betaine, is a popular ingredient in sports supplements that has been claimed to enhance performance and lean mass. This article aims to review the current state of the literature as to the potential ergogenic effects of betaine on muscular strength, power, and body composition and draw evidence-based conclusions as to its use as a sports supplement. Animal models indicate beneficial effects of betaine on improvements in body composition; the literature investigating these effects in humans is promising but limited. There are various mechanisms by which betaine may facilitate increases in muscle strength and power; however, the current literature does not seem to support a beneficial effect on these outcomes. Given that betaine does not seem to be associated with any side effects, its short-term use may be worth considering for athletes seeking improved body composition until further research provides more definitive evidence on the topic. The lack of data on long-term safety warrants caution for its continued use.